KONFLIK SEPARATIS DI MARAWI FILIPINA SELATAN TAHUN 2016-2017 - Lestari, Sinta Ayu (Solidaritas: Jurnal Ilmu-Ilmu Sosial, 2020)
This study discusses about the separatist conflict in Marawi, South Philippines in 2016-2017. The failure of the peace process in the Philippines encouraged the growth of terrorism into the ASG and the Maute Group that wanted to establish a wilayat in Marawi as a fortess of ISIS in Southeast Asia. This effort triggered a battle with the Philippines military. The purpose of this study is to describe how the separatist conflict in Marawi City, southern Philippines developed. This research uses qualitative method with interviews as primary data and literature study as secondary data. In this study the author used conflict theory and conflict mapping theory. The result of this research is Moro Muslims feel discriminated against by the Philippine government because of religious differences, bad experiences in the past have triggering formed of Muslim separatist groups in the Philippines, and the entry of ISIS ideology in the ASG and Maute Groups. Keywords: Separatist conflict, Marawi City, Abu Sayyaf Group, Maute Group.